Investigation of Matric Suction in Soil on Alkaline Water - Azmir, Suwaibah Aslamiyyah; Abu Talib, Zaihasra (Recent Trends in Civil Engineering and Built Environment, 2024)
Rainfall has been identified as causes of the slope failures and landslides. The majority of slope failures happened after rain, and the failure was mostly due to the loss of matric suction in soil by rainwater. Matric suction also affected the behavior of unsaturated soils in terms of permeability and shear strength. The purpose of this study is to determine the matric suction in soil with different pH value of water and compared with matric suction in soil with natural water. Main material that have been used was kaolin as soil, and calcium hydroxide as chemical substance for alkaline water. Tensiometer was used to measure the matric suction. The pH alkaline water that has been used in this experiment was 9.04, 10.03 and 11.01. While pH value for natural water is 6.45. The experiment was carried out at Geotechnic Laboratory and Environment Laboratory. The result shows matric suction in soil with calcium hydroxide give high matric suction compared with soil without calcium hydroxide. The highest matric suction recorded as 40 kPa for highest pH value of water which is 11.01. The additional of calcium hydroxide not only can causes the decreasing size of pores, but also can increase the matric suction in soil. By adding calcium hydroxide in soil may reduce the matric suction and improve the slope stability of soil.